High?resolution hydrological?hydraulic modeling of urban floods using infoworks icm - Sidek L.M.; Jaafar A.S.; Majid W.H.A.W.A.; Basri H.; Marufuzzaman M.; Fared M.M.; Moon W.C. (MDPI, 2023)
digital terrain model; flood control; flood forecasting; hydraulics; hydrological modeling; runoff; synthetic aperture radar; Malaysia